2018
DOI: 10.1002/mar.21109
|View full text |Cite
|
Sign up to set email alerts
|

The preference for scarcity: A developmental and comparative perspective

Abstract: Human adults often show a preference for scarce over abundant goods. In this paper, we investigate whether this preference was shared by 4‐ and 6‐year‐old children as well as chimpanzees, humans’ nearest primate relative. Neither chimpanzees nor 4‐year‐olds displayed a scarcity preference, but 6‐year‐olds did, especially in the presence of competitors. We conclude that scarcity preference is a human‐unique preference that develops as humans increase their cognitive skills and social experiences with peers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 55 publications
3
45
0
1
Order By: Relevance
“…That peanut quantity did not lead to discernible differences in feeding behavior could be an indication that food scarcity or abundance does not affect co‐feeding behavior in chimpanzees. This finding substantiates recent experimental work with chimpanzees and children which found, at least in chimpanzees and 4‐year‐old children, no evidence of heightened value‐attributions toward items presented as scarce versus abundant, even in the context of competitors (John et al, ). On the other hand, 6‐year‐old children in the same study paradigm did show a strong scarcity preference, especially in the context of competitors, leading the authors to conclude that this preference develops uniquely in human ontogeny and is not shared by chimpanzees.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…That peanut quantity did not lead to discernible differences in feeding behavior could be an indication that food scarcity or abundance does not affect co‐feeding behavior in chimpanzees. This finding substantiates recent experimental work with chimpanzees and children which found, at least in chimpanzees and 4‐year‐old children, no evidence of heightened value‐attributions toward items presented as scarce versus abundant, even in the context of competitors (John et al, ). On the other hand, 6‐year‐old children in the same study paradigm did show a strong scarcity preference, especially in the context of competitors, leading the authors to conclude that this preference develops uniquely in human ontogeny and is not shared by chimpanzees.…”
Section: Discussionsupporting
confidence: 90%
“…With a focus on how behavior is affected by competition within specific feeding bouts, evidence has been found for increased competition among wild chimpanzees while feeding from small patches in comparison to large patches of fruit, leading to the conclusion that “the relative severity of feeding competition compared to the possible benefits of sociality will vary with the distribution and abundance of food” (White & Wrangham, , p. 148). Indeed, competition has been shown to be higher for scarce in comparison to abundant resources in humans as well (e.g., Gault, Meinard, & Courchamp, ; John, Melis, Read, Rossano, & Tomasello, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Study 3, we continued tracing the development of such a bias, by moving to older participants, namely 3‐ to 6‐year‐olds. These were ages previously found to capture potential changes in children’s scarcity bias (Diesendruck et al, ; John et al, ). Given that the procedure used in Study 2 showed more promise for revealing a scarcity bias, in Study 3 we adopted the same procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Although providing important information on the development of a scarcity bias, the above studies left a number of questions still open. First, the youngest age at which some children (i.e., boys in a noncompetitive scenario, see John et al, ) manifested a scarcity bias was 6 years of age—an age that leaves unclear as to whether this development derives from sociocognitive achievements underlying the need for uniqueness account of scarcity bias, or from socioeconomic understanding underlying derived accounts. Second, some of the tasks involved a number of other factors besides “pure” scarcity (e.g., the presence of competitors, quality of items), also clouding the possible conclusions derivable from the findings.…”
mentioning
confidence: 99%
“…Moreover, when companies invest together, they both have a greater interest in maintaining the relationship (Morgan & Hunt, 1994). Thus, the scarcity of alternatives increases the preference for the available alternative (M. John, Melis, Read, Rossano, & Tomasello, 2018). The increase in preference for the alternative is based on the fear of losing an opportunity, especially when dealing with uncertainties in the presence of competitors.…”
Section: Comparison Level Of Alternativesmentioning
confidence: 99%